Keratoconus Diagnosis and Treatment - Das, Sujata; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book covers various aspects of the management of keratoconus, which is a leading cause of visual impairment in young adults. It focuses on the epidemiology and risk factors of keratoconus with a special focus on Southeast Asia. Keratoconus affects the quality of vision, thereby affecting the quality of life. While most patients present with defective vision, many are diagnosed accidentally during screening for refractive surgery. The book covers the varied epidemiology of keratoconus across different parts of the world. It discusses many systemic and ocular diseases associated with keratoconus. The book covers the newer diagnostic techniques and various treatment procedures for keratoconus, helping in diagnosing keratoconus in the early stages and closely watching the progression. It discusses various contact lenses to improve vision quality; widely used collagen crosslinking, and its various modifications for halting the progression. It also explains the surgical approach for keratoconus, such as penetrating keratoplasty, lamellar keratoplasty and other lens-assisted procedures. The book is relevant for general ophthalmologists and cornea specialists.
Epidemiology of Keratoconus -- Etiology and Risk Factors of Keratoconus -- Biomechanics of Keratoconus -- Pathophysiology and Histopathology of Keratoconus -- Clinical Diagnosis of Keratoconus -- Classifications and Patterns of Keratoconus -- Differential Diagnosis of Keratoconus -- Keratoconus in Children -- Allergic Eye Disease and Keratoconus -- Topography and Tomography of Keratoconus -- Newer Diagnostic Technology for Diagnosis of Keratoconus -- Risk Factors and Management of Acute Corneal Hydrops in Keratoconus -- Contact Lenses for Keratoconus -- Corneal Cross-linking in Keratoconus -- Penetrating Keratoplasty in Keratoconus -- Lamellar Keratoplasty in Keratoconus -- Intracorneal Ring Segments in Keratoconus -- Intraocular Lens (IOL) Implantation in Kertaoconus -- Stromal Augmentation Techniques for Keratoconus -- Cataract Surgery in Keratoconus -- Refractive Surgery in Management of Keratoconus -- Artificial Intelligence in the Diagnosis and Management of Keratoconus -- Changing Paradigm in the Diagnosis and Management of Keratoconus.
Keywords: Ophthalmology; Ophthalmology; Keratoconus -- diagnosis; Keratoconus -- therapy